Bubbled RNA-Based Cargo for Boosting RNA Interference - Kim, Hyejin; Jeong, Jaepil; Kim, Dajeong; Kwak, Gijung; Kim, Sun Hwa; Lee, Jong Bum (WILEY, 2017)
As ribonucleic acid (RNA) nanotechnology has advanced, it has been applied widely in RNA-based therapeutics. Among the range of approaches, enzymatically synthesized RNA structures for inducing RNA interference in cancer cells have potential for silencing genes in a target-specific manner. On the other hand, the efficiency of gene silencing needs to be improved to utilize the RNA-based system for RNAi therapeutics. This paper introduces a new approach for efficient generation of siRNA from bubbled RNA-based cargo (BRC). The presence of bubbles in between to avoid nonfunctional short dsRNAs allows the RNA-based cargoes to contain multiple Dicer-cleavage sites to release the functional siRNAs when introduced to cells. BRCs can be synthesized easily in a one-pot process and be purified by simple centrifugation. Furthermore, efficient target gene silencing by the bubbled structure is confirmed both in vitro and in vivo. Therefore, this bubbled RNA cargo system can be utilized for target-specific RNAi therapeutics with high efficiency in the generation of functional siRNAs in the target cells.
Keywords: SIRNA DELIVERY; DNA; NANOPARTICLES; NANOTECHNOLOGY; TRANSCRIPTION; OLIGONUCLEOTIDES; MICROSPONGES; THERAPEUTICS; CHALLENGES; GENERATION